The impact of coffee consumption on osteoarthritis: insights from NHANES and Mendelian randomization analysis - Feng, Kai; Li, Peng; Guo, Haohui; Chen, Zhirong (Frontiers in Nutrition, 2024)
Background Osteoarthritis (OA) is a prevalent degenerative joint condition, and emerging evidence suggests that dietary factors, such as coffee consumption, may influence its risk. However, the relationship between coffee consumption and the risk of developing OA remains ambiguous. This study aims to explore the association between coffee intake and OA complemented by Mendelian randomization (MR) to infer causality. Materials and methods We analyzed data from 32,439 participants across 10 NHANES cycles (1999–2018), including 3,676 individuals diagnosed with OA. Osteoarthritis was diagnosed through a structured questionnaire, while coffee consumption was assessed via 24-h dietary recalls. Participants were categorized based on reported coffee intake: 0 cups, <2 cups, 2–4 cups, and >4 cups per day. We employed weighted multivariable logistic regression to examine associations between coffee consumption and OA by using data from the NHANES 1999–2018, adjusting for various covariates. Subsequently, a MR analysis was conducted using genetic variants as instrumental variables to infer causal relationships, with multiple methods including inverse-variance weighted (IVW) analysis, MR-Egger regression, and weighted median techniques to assess the robustness, heterogeneity, and potential pleiotropy of our findings. Results Our regression models indicated an increased risk of OA with rising coffee consumption, with significant associations noted particularly for those consuming more than 4 cups daily (OR = 1.19, 95% CI: 1.00–1.41, p = 0.049). In MR analysis, coffee intake was causally linked to OA types, demonstrating increased risk for knee OA (KOA: OR = 1.60, 95% CI: 1.08–2.35, p = 0.018), hip OA (HOA: OR = 1.85, 95% CI: 1.06–3.25, p = 0.031), and combined KOA and HOA (KHOA: OR = 1.66, 95% CI: 1.18–2.33, p = 0.003). Sensitivity analyses confirmed the stability of results across multiple evaluation methods. Conclusion Our findings highlight a significant association between coffee consumption and an increased risk of OA, suggesting that higher intake levels may contribute to OA morbidity. These results warrant further exploration into the underlying biological mechanisms and implications for dietary guidelines in populations at risk for OA.